Persekutuan dan relasi kuasa: Sebuah komparasi konsep tata gereja 1987 dan 2007, Gereja Masehi Injili di Halmahera - Botara, Sirayandris (KURIOS, 2025)
The purpose of this study is to demonstrate the differences and similarities in the concepts of fellowship (koinonia) and power relations in the self-organization of the Evangelical Christian Church in Halmahera (GMIH), as articulated in the GMIH Church Orders of 1987 and 2007, both of which explicitly identify themselves as churches adhering to presbyterial-synodal principles. Through qualitative research methods employing library research on the GMIH Church Order documents of 1987 and 2007, it was found that there are fundamental differences between the concepts of fellowship and power relations in these two documents. In the 1987 Church Order, an exclusive nuance of the fellowship concept was identified, as it was interpreted solely as inter-congregational relations within the GMIH Synod; power relations were more structurally hierarchical. In the 2007 Church Order, the interpretation of the fellowship concept (koinonia) is more inclusive and multicultural, as it considers post-conflict reconciliatory social relations in Halmahera and its surrounding islands; power relations emphasize non-hierarchical structures and prioritize equality of power between congregations and between Congregations and the Synod. Nevertheless, both GMIH Church Orders maintain a Christocentric character.   Abstrak Tujuan kajian ini untuk memperlihatkan perbedaan dan persamaan konsep persekutuan (koinonia) dan relasi-kuasa dalam pengorganisasian diri Gereja Masehi Injili di Halmahera (GMIH), sebagaimana tertuang dalam Tata Gereja GMIH 1987 dan 2007, serta mengaku diri secara eksplisit dalam kedua Tata Gereja sebagai Gereja yang berprinsip gereja presbiterial sinodal. Melalui metode penelitian kualitatif dengan jenis penelitian kepustakaan terhadap dokumen Tata Gereja GMIH 1987 dan 2007 ditemukan bahwa ada perbedaan prinsip antara konsep persekutuan dan relasi kuasa di antara keduanya. Dalam Tata Gereja 1987, ditemukan nuansa ekslusif dari konsep persekutuan karena hanya ditafsirkan sebagai relasi antarjemaat dalam Sinode GMIH; relasi kuasa lebih bersifat struktural-hierarkis. Dalam Tata Gereja 2007 pemaknaan konsep persekutuan (koinonia) lebih inklusif dan multikultural karena mempertimbangkan relasi sosial rekonsiliatif pascakonflik di Halamhera dan pulau-pulau sekitarnya; relasi kuasa lebih menekankan non-hierarkhis dan mengedepankan kesetaraan kuasa antarjemaat dan antara Jemaat dan Sinode. Sekalilipun demikian,  kedua Tata Gereja GMIH tersebut memiliki sifat kristosentris.